Effects of Breast-Conserving Surgery Combined with Sentinel Lymph Node Biopsy on Breast Cosmetic Appearance and Systemic Stress of Patients with Breast Cancer - Jing Ji; Junfeng Shi; Xia Da; Guozhu Wang; Jin Xu (Clinical and Experimental Obstetrics & Gynecology)
Background: We aimed to evaluate breast-conserving surgery plus sentinel lymph node biopsy in affecting breast cosmetic appearance and systemic stress of breast cancer patients. Methods: A total of 150 early breast cancer patients admitted between January 2020 and September 2022 were retrospectively analyzed. Propensity score matching was performed to minimize selection bias based on baseline characteristics, resulting in two matched groups of 55 patients each. The observation group received breast-conserving surgery and sentinel lymph node biopsy, while the control group underwent breast-conserving surgery and axillary lymph node dissection. Results: The observation group experienced shortened operation time and extubation time compared with the control group, and there were significantly different blood losses between the two groups (p < 0.05). The observation group was significantly superior to the control group in terms of the postoperative quality of life (p < 0.05). After treatment, the levels of plasma procalcitonin (PCT) and tumor necrosis factor-α (TNF-α) in the two groups decreased. By contrast to those in the control group, PCT, TNF-α, carcinoembryonic antigen and carbohydrate antigen 125 presented significantly reduced levels in the observation group following treatment (p < 0.05). The observation group, compared to the control group, exhibited significant improvement of the breast appearance (p < 0.05). No significant difference was observed between the two groups regarding human epidermal growth factor receptor-2 (HER-2) expression (p > 0.05). Conclusion: Breast-conserving surgery and sentinel lymph node biopsy are simple and can reduce the complications and benefit the recovery of patients.